Mutation HOXB13 c.853delT in Martinican prostate cancer patients. Issue 6 (10th February 2020) - Marlin, Régine; Créoff, Morgane; Merle, Sylvie; Jean‐Marie‐Flore, Magalie; Rose, Mickaelle; Malsa, Sarah; Promeyrat, Xavier; Martin, François; Comlan, Georges; Rabia, Nicolas; Taouil, Taoufiq; Issoufaly, Irfane; et al.
Abstract: Background: In Martinique, prostate cancer (Pca) incidence rates are nowadays among the highest worldwide with a high incidence of early‐onset and familial forms. Despite the demonstration of a strong familial component, identification of the genetic basis for hereditary Pca is challenging. The HOXB13 germline variant G84E (rs138213197) was described in men of European descent with Pca risk. Methods: To investigate the potential involvement of HOXB13 mutations in Martinique, we performed sequencing of the HOXB13 coding regions of 46 index cases with early‐onset Pca (before the age of 51). Additional breast cancers and controls were performed. All cancer cases analyzed in this study have been observed in the context of genetic counseling. Results: We identified a rare heterozygous germline variant c.853delT (p.Ter285Lysfs) rs77179853, reported only among patients of African ancestry with a minor allele frequency of 3.2%. This variant is a stop loss reported only among patients of African ancestry with a frequency of 0.2%. Conclusion: In conclusion, we think that this study provides supplementary arguments that HOXB13 variants are involved in Pca.